THE IMPORTANCE OF EXCLUSIVE BREASTFEEDING IN THE FIRST SIX MONTHS OF LIFE AND THE ROLE OF NURSING - Santos, Amanda Cabral dos; Meireles, Camila Pires (Revista Coleta Científica, 2021)
Exclusive breastfeeding in the first six months of life is advocated in Brazil and in several countries. The problem of this study is: What is the importance of exclusive breastfeeding in the first 6 months of life and what is the role of nursing in this context? The general objective of this study is to describe the benefits of exclusive breastfeeding in the first 6 months of life and the role of nursing in this process. This study is an integrative literature review that brings together scientific articles published from 2010 to 2021. The role of nursing therefore involves information and guidance aimed at education and health promotion, in order to demystify ideas culturally perpetuated by sense that end up interfering negatively in the entire process involving breastfeeding.